Cyclic torsion of AZ31 magnesium alloy rod and its effect on mechanical property - SONG Guang-sheng; JI Kai-sheng; ZHANG Shi-hong (Cailiao gongcheng, 2019)
The cyclic torsion was carried out on the extruded AZ31 magnesium alloy rods at room temperature by using a computer controlled torsion testing machine. The texture of initial extruded magnesium alloy rods was measured by the XRD technique, which displays a typical basal texture. The mechanical properties during deformation were measured, and the microstructure and texture feature after torsion were analyzed by the EBSD. Meanwhile, the effect of cyclic torsion on mechanical properties of magnesium alloy rods was also investigated. The results show that the symmetrical stress-strain hysteresis curves are obtained during the cyclic torsion of magnesium alloy rods, revealing that sliding is the dominant deformation mode during former torsions, moreover, the stress peak values of the hysteresis curves present an increasing first and then decreasing trend with the increase of cycle period, which is dominated by work hardening and internal micro-crack propagation. The stress peak forms at the 4th cycle under conditions of 60ånd 90°maximum torsion angles, respectively. Amounts of extension twinning bands formed within grains after torsion of magnesium alloy rods, c-axis of grains is rotated to the axial direction of bars caused by the activation of twinning. Mechanical properties of twisted magnesium alloy rods tested by computer controlled universal testing machine show that the compression yielding strength of magnesium alloy bars is increased by the cyclic torsion, the value of which is increased from about 100MPa before torsion to about 200MPa after torsion at most.